Pengaruh Permainan Kooperatif dan Kecerdasan Interpersonal terhadap Regulasi Emosi Anak - Tisya Permatasari; Hapidin Hapidin; Karnadi Karnadi (Indonesian Journal of Educational Counseling, 2020)
THE EFFECT OF COOPERATIVE GAMES AND INTERPERSONAL INTELLIGENCE ON CHILD EMOTIONAL REGULATION. Negative actions that occur at this time are much related to one's emotional regulation ability. For this reason, instilling the ability of motion regulations should be prepared early. Interpersonal intelligence children like building, relationships and maintaining social relationships will make it easier to know what kind of emotion regulation affecting children. For this reason, cooperative games have become a good game to do in increasing children's regulation. This study aims to reveal the extent to which the influence of cooperative games and interpersonal intelligence on the regulation of motions. Observational research data were tested using a normality test and a homogeneity test followed by a two-way variance test (ANAVA) and continued testing with tukey testing. The results showed that the sample data were normally distributed and homogeneous. The results of the analysis also showed the existence of the interaction of cooperative games and interpersonal intelligence on regulation based on the results of the analysis of variance F count = 62.52 > F tab = 4.08 at the significant level = 0.05.